Kontribusi Mini Market Pesantren sebagai Potensi Kemandirian Ekonomi dan Pembentukan Jiwa Santripreneur - Najib, Moh. Ainun; Ghafur, Abd; Azizah, Lailatul (Jurnal Informatika Ekonomi Bisnis, 2024)
The background of this research is the development of the times and advances in science and technology which require graduates or boarding school graduates to not only be proficient in the field of religion, but also to be able to compete and have skills and independence and have an entrepreneurial spirit so that in the future they will have a role in developing the economy of the surrounding community. So the role of minimarkets for students is very important to train them in business and doing business. Islamic boarding schools also benefit from the existence of learning media for students in entrepreneurship, both in terms of leadership, management, financial management, and so on. From these various advantages, the economic potential of Islamic boarding schools can be categorized as very useful and contributes to the Indonesian economy. The research method used is qualitative descriptive research. The research object is an Islamic boarding school. The research results show that personal factors in entrepreneurship are seeking profits and creating jobs. The entrepreneurial knowledge gained can produce the mindset and behavior of becoming an entrepreneur. This is supported by the Santri's ability as mentors to create ideas for making new products and are willing to accept suggestions/input from other people to come up with creative and innovative actions.